A Review Study - Dietary Management of Psoriasis - Ali, CM (Bangladesh Medical Journal, 2014)
Psoriasis is a common, chronic, inflammatory scaly rashes associated with T-cell medicated immunological disorder. The cause of psoriasis is unknown but molecular mechanism suggest an immune disorder and the role of genetic and environmental influence. There are activation of T-cells that releases pro-inflammatory cytokines and causes an inflammatory-·reaction in the affected skin. The inflammatory nature of psoriasis itself is associated with an increased cardio-vascular morbidity. Modern trends of diet consisting high amounts of omega-6 fatty acid and low amounts of omega-3 fatty acid which is associated with a pro-inflammatory state. Dietary modification in the treatment of psoriasis may reduce the need of aggressive approaches and improves the cardio-vascular risk f actors associated with psoriasis. This review summarizes the understanding of dietary modification in the management of psoriasis and to achieve a pathogenesis directed dietary approach in the treatment of psoriasis. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18500 Bangladesh Medical Journal 2011 Vol.40(2): 23-25